2019
DOI: 10.12659/msm.911862
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-Mediated Silencing of MicroRNA-211 Decreases the Sensitivity of Melanoma Cells to Cisplatin

Abstract: Background Malignant melanoma is recalcitrant to most existing chemotherapies, and aberrant expression of miR-211 plays prominent roles in progression of melanoma. However, the trigger mechanism of aberrant miR-211 expression in melanoma is still elusive. Material/Methods We used qRT-PCR to test miR-211 expression. Cell viability assay and mouse xenograft assay were performed to examine the role of miR-211 on the sensitivity of melanoma cells to cisplatin. The epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…An existing study identified the ability of EZH2 to repress miR-708 expression by incorporating promoter methylation in the glioma tissues and cells [29]. Likewise, the miR-211 expression was reduced by EZH2-mediated methylation in malignant melanoma [7], and overexpression of EZH2 significantly decreased miR-193a expression in OC [30], which was in compliance with the observed mechanism of EZH2-mediated methylation in our study. Our findings elicited that EZH2 could downregulate the miR-139 expression by engaging H3K27me3 to stimulate the methylation of miR-139 promoter, as proved by the ChIP assay.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An existing study identified the ability of EZH2 to repress miR-708 expression by incorporating promoter methylation in the glioma tissues and cells [29]. Likewise, the miR-211 expression was reduced by EZH2-mediated methylation in malignant melanoma [7], and overexpression of EZH2 significantly decreased miR-193a expression in OC [30], which was in compliance with the observed mechanism of EZH2-mediated methylation in our study. Our findings elicited that EZH2 could downregulate the miR-139 expression by engaging H3K27me3 to stimulate the methylation of miR-139 promoter, as proved by the ChIP assay.…”
Section: Discussionsupporting
confidence: 90%
“…An existing study unraveled that EZH2 played a crucial role in the development of OC [ 6 ]. EZH2 was also reported to affect tumorigenesis by mediating the methylation of microRNA (miR)-211 [ 7 ]. Besides, EZH2 was validated to meditate and influence the insulin-like growth factor 1 receptor by direct transcriptional suppression of miR-139 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the EZH2/DNMT1/MIR211/RAB22A axis might provide novel insights into the molecular pathogenesis of both melanoma and glioblastoma, particularly on the EMT processes in these two different cancers. In a separate study, Li N et al reported that the silencing of MIR211 expression by methylation is associated with reduced cisplatin sensitivity in melanoma ( 39 ). This observation, however, may be interpreted as an indirect consequence of reduced EMT in MIR211 deficient cells, because increased EMT increases the resistance of cells to cisplatin ( 40 ).…”
Section: The Epigenetic Regulation Of Mir211mentioning
confidence: 99%
“…Besides genetic variations, epigenetic changes or post-transcriptional modifications of miRNAs can lead to deregulated expression in tumor cells [255]. For example, DNA hypermethylation can initiate the downregulation of miR-211 in melanoma tissue, which is a tumor-suppressive miRNA and suppressed in melanoma [256]. In HCC, numerous tumor-suppressive miRNAs including miR-1, miR-124 and miR-203 are downregulated during hepatocarcinogenesis as a result of promoter hypermethylation [257].…”
Section: Genetic Alterations Transcriptional Regulation and Mirna-edmentioning
confidence: 99%